The human factors associated with responding to emergency vehicles - Grant, Pauline (2017)
Emergency vehicles undertake emergency driving, using lights and sirens, to move rapidly through traffic in response to situations where life and property are at risk. For the emergency driving to be effective, other motorists need to drive in a manner that facilitates their passage. Despite laws to support this, problematic encounters can result in emergency vehicles being unable to get through. The current research expanded on earlier exploratory research into motorists’ encounters with emergency vehicles (Grant, 2010) to examine psychological factors involved with motorists’ responses to emergency vehicles. A construct validity approach was used to develop a scale through which a larger representative sample could be assessed. A qualitative study with emergency service drivers and motorists combined with existing literature to provide the basis for the scale development, and the subsequent testing and refinement resulted in the Responding to Emergency Vehicles Scale (REVS). The data obtained throughout development of the scale, from 1089 participants, were used to investigate psychological factors associated with responding to emergency vehicles and have identified the following overarching factors: Reasons for responding to emergency vehicles; attitudes and beliefs about emergency vehicles/services; appraisal of the encounter and their ability to respond; prior associations with emergency services personnel, or vehicles; and beliefs around punishment. The study also explored participants’ demographic factors relative to their reported driving behaviours during emergency vehicle encounters. Lastly, it identified the needs of the emergency service drivers during encounters, suggesting that existing road safety messages were inconsistent with actual needs of emergency service drivers, and suggested an alternative model of response. Overall, the psychological factors provided an understanding of the participants’ aptitude to be trained to respond more effectively. Their strong pro-social intentions indicated an intention to respond appropriately to emergency vehicles and they were cognisant of the potential consequences of not doing so. Their generally positive views about emergency vehicles as well as associated services, and beliefs in the appropriateness of punishment further supported their willingness to respond appropriately. Finally, participants reported that they were aroused by emergency vehicles encounters, but not stressed to the extent they were incapable of responding. Whilst the research was undertaken from a predominately theoretical lens, the applied nature of the phenomenon under scrutiny yielded findings that can inform policy around responding to emergency vehicles. Specifically, the findings suggest the need to embed explicit training on emergency vehicles within the existing driver training framework. They also recommend amendment to the road safety message used to guide motorists’ actions during encounters with emergency vehicles. Future studies could confirm the appropriateness of the recommended response model with a larger sample of emergency service drivers, and use the REVS to assess larger samples and different driving populations